Status of behavioral medicine in American and Canadian medical training - Margolis, R B; Duckro, P N; Sata, L S; Merkel, W T (International journal of psychiatry in medicine, 1987)
This article reports a survey of attitudes and current practices regarding behavioral medicine in American and Canadian medical school departments of psychiatry. Participants were eighty-two chairpersons of departments of psychiatry. Five major areas were addressed concerning the existence, location, and composition of behavioral medicine faculty and their contribution to training and research programs. Results indicate that behavioral medicine is represented in the majority of medical schools and teaching hospitals. Faculty tended to be located in psychiatry. A majority of the respondents did not think that behavioral medicine should be considered a separate clinical specialty area, but in actual practice behavioral medicine was distinct from consultation/liaison psychiatry as often as integrated with it. The analysis of subjects and methods taught in residency training programs suggested a meaningful trend in the data. The implications of these results for models underpinning traditional medical education and psychosomatic medicine are discussed.